QORAQALPOQ XALQINING ZAMONAVIY NIKOH TO‘YI MAROSIMLARINING TRANSFORMATSIYALASHUV JARAYONLARI VA MILLIY MA’NAVIYAT - Bekjanova, B.K. (SCIENCE and SOCIETY, 2024)
The article is devoted to the problems associated with our wedding ceremonies. The issues related to the conduct of wedding ceremonies in accordance with the requirements of the time, national and religious traditions are highlighted. The events held by our state to streamline wedding celebrations, as well as the content and significance of the adopted by-laws were also highlighted.